Case report: Eculizumab plus obinutuzumab induction in a deceased donor kidney transplant recipient with DEAP-HUS - Favi, Evaldo; Molinari, Paolo; Alfieri, Carlo; Castellano, Giuseppe; Ferraresso, Mariano; Cresseri, Donata (Frontiers in Immunology, 2022)
The wide-spread use of the anti-complement monoclonal antibody (moAb) eculizumab has greatly reduced the incidence of relapsing atypical hemolytic uremic syndrome (aHUS) after kidney transplantation (KT). However, the optimal management of aHUS transplant candidates with anti-Complement Factor H (CFH) antibody remains debated. In these patients, the benefits of chronic eculizumab administration should be weighed against the risk of fatal infections, repeated hospital admissions, and excessive costs. We report the case of a 45-year-old woman with CFHR1/CFHR3 homozygous deletion-associated aHUS who underwent deceased-donor KT despite persistently elevated anti-CFH antibody titers. As induction, she received a combination of eculizumab and obinutuzumab, a humanized anti-CD20 moAb. The post-operative course was uneventful. At 1-year of follow-up, she is doing well with excellent allograft function, undetectable anti-CFH antibody, sustained B-cell depletion, and no signs of aHUS activity. A brief review summarizing current literature on the topic is also included. Our experience suggests that obinutuzumab can block anti-CFH antibody production safely and effectively, thus ensuring long-lasting protection from post-transplant aHUS relapse, at a reasonable cost. For the first time, we have demonstrated in vivo that obinutuzumab B-cell depleting properties are not significantly affected by eculizumab-induced complement inhibition.